Studying the bivariate tacticity distribution of poly-1-octene using two-dimensional liquid chromatography coupled with NMR. (12th June 2019) - Rode, Karsten; Malz, Frank; Arndt, Jan-Hendrik; Macko, Tibor; Horchler, Gordian; Yu, Youlu; Brüll, Robert
Abstract: The application properties of poly-1-olefins depend on their molar mass and the microstructure i.e., tacticity. While average values for the latter are available from NMR, its distribution along and across the molar mass axis is not yet accessible. Two samples of poly-1-octene with different average tacticity were chosen for the investigation with liquid chromatography and off-line NMR detection. Because of the relatively low molar mass of the samples, liquid adsorption chromatography (LAC) is then a function of two parameters i.e., molar mass and tacticity. To study the tacticity distribution independent from the molar mass, samples were first preparatively fractionated by size-exclusion chromatography (SEC). Analysis of the SEC fractions showed a gradient of tacticity along the molar mass axis. The isolated SEC fractions were then preparatively separated by LAC using porous graphite as stationary phase. NMR analysis of the LAC fractions then revealed a fractionation according to tacticity. Notably, two distinct populations that differ in tacticity were shown, which may be a result of different polymerization pathways. A comparison of the experimental results with theoretical calculations confirms that the configuration of the macromolecules in solution determines the retention on the stationary phase in LAC. Graphical abstract: Image 1 Highlights: Tacticity distribution of polyalphaolefins studied with SEC, HPLC and off-line NMR detection. Fractions prepared with SEC were separated with HPLC and tacticity of HPLC fractions was determined with NMR spectroscopy. NMR analysis of the HPLC fractions revealed a fractionation according to tacticity of poly-1-octene.